AN ALGORITHM FOR ORGANIZING AND GROUPING DATA RELATED TO THE EXPENDITURESBY EDUCATION LEVELS - Delyana DIMOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper presents an algorithm for organizing and grouping data related to the expenditures by education levels in Bulgaria. The built database is used as a source from which the necessary information is searched depending on the entered indicators and time interval.The considered indicators include the public and private expenditures by education levelsfor the period2012-2020.The extracted subsets of elements are processed and analyzed. In this connection, four groups of variables are calculated and discussed.The results show that the expenditures in four of the education levels (primaryand pre-primary education as well as upper and lower secondary education) grow over the last five years (2016-2020). The quoted indicator inpost-secondary, non-tertiary education isreduced gradually in 2016-2019. During 2015, as compared to 2014, the expenditures in the considered 7 levels of education decreased in the range from 0.29% to 7.81%.This work calculates the share of expenditure for tertiary education-bachelor, master and doctor in comparison with the totalexpendituresfor educationinthe indicatedtime period. The obtained value of the variable for this education level is the highest. It is 29.74%. The values of this variable are significantly lower for the following two levels of education - tertiary education-professional bachelor and post-secondary, non-tertiary education. They are 1.54% and 0.29% respectively.